Lecturer And Student Perceptions Of The Merdeka Belajar Kampus Merdeka Program In Higher Education Institutions In Tasikmalaya - Darusman, Yus; Hamdan, Ahmad; Laksono, Bayu Adi (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to explore the perceptions of lecturers and students regarding the Merdeka Belajar Kampus Merdeka (MBKM) Program in higher education institutions in Tasikmalaya. Using a quantitative approach, this research employed a survey method involving 152 students and 40 lecturers from several universities in Tasikmalaya. The research instrument was a structured questionnaire using a 5-point Likert scale to measure understanding, clarity of information, alignment of the program with Learning Outcome Standards, and the program's impact on student competencies. The results showed that the majority of respondents, both lecturers and students, had a good understanding of the MBKM concept and considered the information provided by their institutions to be sufficiently clear. A total of 82.9% of students stated that the program aligned with their future plans, while 84.6% of lecturers believed that the MBKM program positively contributed to improving student competencies. However, a small group of respondents expressed doubts regarding the clarity of information and the program’s alignment. This study provides deep insights into the perceptions of MBKM implementation and offers recommendations for improving the program’s quality to more effectively support student development.